The Efficiency of Algorithms and Number of Control Hierarchy Levels of Building Electronic Control System - Keras, E. (Elektronika ir Elektrotechnika, 2013)
In the paper the building electronic control systems (BECS) are introduced, existing trends of their development are identified, and related important efficiency research problems are defined, their factors are distinguished which strongly influence the operation of entire BECS methods of efficiency evaluation of selecting operation algorithm and hierarchical control levels. General diagram of factors impacting general i-th component of algorithm is presented, parameters of these factors are indicated, and it is also demonstrated, that the values of these parameters are independent of each other. Methods are offered how to select optimal numbers of BECS hierarchical levels. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5395